Mariner-like transposases are widespread and diverse in flowering plants - Feschotte, Cédric (The National Academy of Sciences, 2002)
Complete and partial sequences of mariner-like elements (MLEs) have been reported for hundreds of species of animals, but only two have been identified in plants. On the basis of these two plant MLEs and several related sequences identified by database searches, plant-specific degenerate primers were derived and used to amplify a conserved region of MLE transposase genes from a variety of plant genomes. Positive products were obtained for 6 dicots and 31 monocots of 54 plant species tested. Phylogenetic analysis of 68 distinct MLE transposase sequences from 25 grass species is consistent with vertical transmission and rapid diversification of multiple lineages of transposases. Surprisingly, the evolution of MLEs in grasses was accompanied by repeated and independent acquisition of introns in a localized region of the transposase gene.